A time-series method for MODIS aerosol optical depth retrieval - Broomhall, Mark Anthony (Curtin University, 2014)
Aerosol Optical Depth [AOD] is an important input for the atmospheric correction of satellite-derived Earth Observation data, and remains the most difficult variable to properly quantify. The Reflectance Change method utilises time-series data from a Bidirectional Reflectance Distribution Model to estimate the surface reflectance which is used as an input into the AOD retrieval model. This approach moves away from previous methods that use band ratio techniques, which are problematic over characteristically arid Australian landscapes.